Rendering unto Caesar : the Catholic Church and the state in Latin America - Gill, Anthony James (University of Chicago Press, 1998)
Nowhere has the relationship between state and church been more volatile in recent decades than in Latin America. Anthony Gill's controversial book not only explains why Catholic leaders in some countries came to oppose dictatorial rule but, equally important, why many did not.